COVID-19 and Vaccine Hesitancy: A Challenge the United States Must Overcome. Issue 1 (January 2021) - Coustasse, Alberto; Kimble, Craig; Maxik, Kenneth
Abstract : A significant portion of the U.S. population may experience vaccine hesitancy of a new COVID-19 vaccine, which poses dangers to both the individual and their community, since exposure to a contagious disease places the person at risk, and individuals are far more likely to spread the disease to others if they do not get vaccinated. Many individuals are doubtful, and without the healthcare community, speaking with one voice has led to distrust. Experience from the influenza vaccines have shown vaccine acceptance has not been optimal, and this new vaccine, even though it is not approved, is already showing layperson skepticism compounded by political influences.